Risk analysis of antimicrobial resistance in outpatient urinary tract infections of young healthy adults. (23rd October 2018) - Brosh-Nissimov, Tal; Navon-Venezia, Shiri; Keller, Nathan; Amit, Sharon
Abstract: Objectives: Most studies addressing community-acquired urinary tract infections (UTIs) pertain to mixed cohorts, in which young healthy adults are under-represented. We aimed to dissect the intricate interrelation between exposures and subsequent antimicrobial resistance (AMR) patterns in a unique setting of young healthy adults, allowing further guidance in this group. Methods: We carried out a retrospective cross-sectional study of all Enterobacteriaceae-associated outpatient UTIs during 2014–16 in soldiers, representing the young fit population in Israel. Electronic medical records were reviewed for demographic and clinical data, antimicrobial exposures and prescriptions. Risk factors for AMR were analysed by multivariate logistic regression. Results: Of 1207 cases, 1144 (94.8%) were females, with a median age of 20.2 years. Escherichia coli was the predominant species (83.2%). Only 686 (56.8%) isolates were fully susceptible. AMR rates were as follows: trimethoprim/sulfamethoxazole, 19.6%; oral cephalosporins, 9.7%–16.7%; amoxicillin/clavulanate, 12.1%; ciprofloxacin, 11.1%; and nitrofurantoin, 12.6%. Predictors of AMR were recurrent UTIs, past-year hospitalization, male gender and non E. coli strains. Antimicrobials prescribed >6 months preceding the culprit infection were not related to AMR. Fluoroquinolone and cephalosporin exposures were highly predictive of further AMR, yet nitrofurantoin and, to a lesser extent, amoxicillin/clavulanate had fewer associations with AMR induction and resistance to these antimicrobials was less associated with any exposure. Conclusions: This nationwide study of community-related UTIs shows significant AMR rates for commonly used oral antimicrobials even in young fit adults. Nitrofurantoin proved once more to be an adequate empirical choice regardless of previous exposures, having a less detrimental effect on future AMR. Conversely, both resistance to fluoroquinolones following previous exposures and the associated heavy ecological burden should deter their common use as first-line agents for UTIs.